A methodology for the engineering design and analysis of foreshore basins for beach erosion protection. - Cruz, Eric C.
The conceptual design of a beach as a resort amenity is brought one level higher by considering a beach to be part of a foreshore basin. The basin is designed as an engineered tide pool to promote deposition of sediments on the beach while satisfying an imposed requirement on the frequency of seawater replenishment. The basin structure is designed to withstand wave loadings from tropical storms, while meeting the requirements for seawater replacement frequency, suitable depth for beach swimming and the need to promote sediment deposition within the basin. The methodology proposed includes the procedure for tide penetration analysis, sediment stability analysis and the hydraulic analysis and engineering design of the basin structure against typhoon-induced wave loadings.
Keywords: Foreshore basin; Beach tides; Waves; Erosion